Electrical, optical, thermoelectric power, and dielectrical properties of organic semiconductor poly(1,12-bis(carbazolyl) dodecane) film - Yakuphanoğlu, Fahrettin; Liu, Houting; Xu, Jingkun (Amer Chemical Soc, 2007)
Electrical conductivity, optical, thermoelectric, and dielectrical properties of the poly(1,12-bis(carbazolyl) dodecane) film have been investigated. The activation energy for electrical conductivity and room-temperature electrical conductivity (at 25 degrees C) values were found to be 0.25 eV and 2.65 x 10(-6) S/cm, respectively. The thermoelectric power results suggest that the conductivity is due to large polarons (i.e., the carriers in polymer move by hopping in the localized states at band gap edges). Electrical conductivity and thermoelectric power results confirm that the polymer is a p-type organic semiconductor. Optical absorption results suggest that the direct allowed transitions are dominant in the fundamental absorption edge in the polymer with optical band gap value of 2.72 eV. The refractive index dispersion of the polymer obeys the single oscillator model with oscillator energy (E-o = 3.06 eV) and dispersion energy (E-d = 17.82 eV) values. Alternating current conductivity results suggest that the hopping conductivity is dominant in the polymer. The dielectrical properties exhibit a non-Debye relaxation.
Keywords: Conductivity; Carbazole; Polymers